A cross-channel color image encryption algorithm using two-dimensional hyperchaotic map - Lai, Qiang; Liu, Yuan (Expert systems with applications, 2023)
This paper innovatively proposes a high-sensitive cross-channel color image encryption algorithm (SFHM-IEA) by using two-dimensional hyperchaotic map (2D-SFHM) derived from Sine map and mathematical function. The performance of the proposed map is numerically investigated, and the results show that 2D-SFHM has larger Lyapunov exponents (up to 8.766), more stable sample entropy, C0 complexity and permutation entropy (all almost 1) than other existing chaotic maps, which indicates that the chaotic sequences generated by 2D-SFHM are highly stochastic. Then a cross-channel color image encryption algorithm combining peripheral-pixel extension technique is proposed, which uses circular-shift permutation and bidirectional-parallel diffusion to obtain strong confusion and diffusion properties. The experimental result with chi-square=229.2843, Pearson correlation coefficient and mutual information are almost 0, information entropy can reach 7.9998, average NPCR=99.6098% and average UACI=33.4632%, which proves the ability of the proposed algorithm to securely resist various illegal attacks. •A new large-scale hyperchaotic map is constructed and its performance is tested.•A new chaos-based cross-channel color image encryption algorithm is designed.•The secure performance of the proposed image algorithm is thoroughly analyzed.